1978
DOI: 10.1093/ajcn/31.6.955
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and social correlates in iron deficiency anemia

Abstract: This study was designed to ascertain some nutrition and nutrition related social factors in the environment of the child with anemia. In this study, it was found that the child with iron deficiency anemia consumed less iron per kilogram per day, drank more milk, was less likely to have been given supplemental iron, was introduced to strained foods at an older age, and had a greater number of siblings. The mother was more likely to be separated or divorced, view the child as having more feeding problems and be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
1
12
0
3
Order By: Relevance
“…Czajka-Narins also reported that a greater number of siblings is a risk factor for anemia. [40] This may be due to distribution of scarce resources within the family, and such conclusion warrants further research. Paternal occupation is an indirect indicator of socioeconomic status of the family in India as most women in rural India are involved in economically nonproductive work.…”
Section: Discussionmentioning
confidence: 95%
“…Czajka-Narins also reported that a greater number of siblings is a risk factor for anemia. [40] This may be due to distribution of scarce resources within the family, and such conclusion warrants further research. Paternal occupation is an indirect indicator of socioeconomic status of the family in India as most women in rural India are involved in economically nonproductive work.…”
Section: Discussionmentioning
confidence: 95%
“…Em contraste com a baixa prevalência mundial de anemia na infância, constatou-se que a prevalência de ADF em crianças que habitam a periferia de grandes cidades norteamericanas é similar à prevalência de ADF observada em países em desenvolvimento 5 . Além disso, vários estudos têm demonstrado uma visível correlação entre deficiência de ferro e anemia e uma série de determinantes, tais como excesso de co-habitantes 6,7 , baixa escolaridade da mãe 8 , alta incidência de parto por cesárea 8 , baixa escolaridade do pai 9 , baixa renda familiar 7,10 e baixas condições socioeconômicas 11 . Assim, é fundamental que se entenda os fatores de riscos de cada população para que se possa oferecer medidas eficazes de prevenção e controle.…”
unclassified
“…How ever Duggan et al found no correlation between biochemical iron status and protein energy nutritional status 14 . However other studies support the view that deficient iron intake is important contributor for low haemoglobin in infancy and early childhood 17,18 . In the studied population haemoglobin was normally distributed and there was no skewness.…”
Section: Fig-1: Distribution Of Haemoglobin In Studied Populationmentioning
confidence: 82%